2011
DOI: 10.4081/ijas.2011.e48
|View full text |Cite
|
Sign up to set email alerts
|

The effects of preparing methods and enzyme supplementation on the utilization of brown marine algae (Sargassum dentifebium) meal in the diet of laying hens

Abstract: Brown marine algae (BMA; Sargassum dentifebium) were collected from Jeddah on the shores of the Red Sea and sun dried at an average daily temperature of 40°C until constant weight was obtained. Part of the sun dried brown marine algae was subsequently processed by boiling (BBMA; boiled brown marine algae) in water and by autoclaving (ABMA; autoclaved brown marine algae). The SBMA, BBMA and ABMA were included in laying hen diet during weeks 23-42 of age at concentrations of 0.0%, 3.0% and 6.0%. The diets were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
2
6
0
1
Order By: Relevance
“…The higher weight, broken eggs (%) and lower eggshell quality of eggs from source A could be attributed to older hens' age of this group as the hens was on production for 18 months when eggs were collected from the market than that of the other groups 6-10 months in production. On the other hand, the values of eggshell quality criteria found herein are within the range of those retrieved by several authors (Kiiskinen and Helander, 1998;UDSA, 2000;Ahmadi and Rahimi, 2011;Al-Harthi and El-Deek, 2011;Alsaffar et al, 2013). Differences in eggshell quality of laying hens could be expected due to concentrations of dietary calcium, phosphorus and vitamin D3, Mn, strain, age, husbandry and management of hens (Attia et al, 1994;Zita et al, 2009), water quality, dietary protein levels, Egg quality in the retail market fat/fatty acid contents, health status and environmental stress of layers (Attia et al, 2009;Ahmadi and Rahimi, 2011;Alsaffar et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The higher weight, broken eggs (%) and lower eggshell quality of eggs from source A could be attributed to older hens' age of this group as the hens was on production for 18 months when eggs were collected from the market than that of the other groups 6-10 months in production. On the other hand, the values of eggshell quality criteria found herein are within the range of those retrieved by several authors (Kiiskinen and Helander, 1998;UDSA, 2000;Ahmadi and Rahimi, 2011;Al-Harthi and El-Deek, 2011;Alsaffar et al, 2013). Differences in eggshell quality of laying hens could be expected due to concentrations of dietary calcium, phosphorus and vitamin D3, Mn, strain, age, husbandry and management of hens (Attia et al, 1994;Zita et al, 2009), water quality, dietary protein levels, Egg quality in the retail market fat/fatty acid contents, health status and environmental stress of layers (Attia et al, 2009;Ahmadi and Rahimi, 2011;Alsaffar et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…This negative correlation could be attributed to spread in the amount of pigmentation (lutein and zeaxanthin) over the surface area of yolk which increased with increasing egg weight and age of hens. Differences in yolk colour could be expected practically due to dietary pigmentation such as zeaxanthin and lutein, and age of hens (Attia et al, 1994;Ahmadi and Rahimi, 2011;Al-Harthi and El-Deek, 2011;Alsaffar et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Chicks had BA in fresh water have heavier carcass weight (1666.67 vs. 1480g), but the relative weight of carcass traits studied was not significantly affected by dietary treatments (ranged between 81.30 vs. 79.99) at 5 weeks. These results are in agreement with El-Deek et al (2011) who showed that using different levels of algae in broiler finisher diets had in significant effect on dressing percentages, gizzard and spleen percentages at 39 days of age. Also, Kovac et al (2013) noted that small amounts of algae used in feeding at different animals, have been created to improve the immune system, increasing weight, number of eggs, improving reproductive performance or reducing cholesterol levels, indicating the possibility of new farming methods in order to improve the quality of meat and eggs.…”
Section: Carcass Characteristicssupporting
confidence: 93%
“…Kritchevsky et al (1999) and Hassan et al (2005) noted that brown meal algae (BMA) showed a beneficial effect on plasma high-density lipoprotein cholesterol (HDL), lowdensity lipoprotein (LDL), total cholesterol and triglycerides which could be attributed to algae sterols. Rimber (2007) and El-Deek et al (2011) found that algae were a valuable human and animal nutrition because of its protein, amino acid, fiber minerals, fatty acids and bioactive content. Jimenez- Escrig and Cambrodon (1999) revealed that revealed that this might be due to its sterol and poly sachcarides content (alginic acid, fucoidan, cellulose, xylose and glucouronic acid).…”
Section: Blood Parametersmentioning
confidence: 99%
“…Reports in the literature found algae was a valuable ingredient in human and animal nutrition because of its protein, amino acid, dietary fibre, mineral, fatty acid and bioactive content (Serviere-Zaragoza et al, 2002;Rimber, 2007;Al-Harthi and El-Deek, 2011). The present results (Table 2) indicate that BMA is a good source of UFA and PUFA which offer several health benefits (Abd ElBaky et al, 2008).…”
Section: Discussionmentioning
confidence: 99%